PERAN GENDER ORANG TUA-REMAJA DALAM FUNGSI KELUARGA DAN KESEJAHTERAAN SUBJEKTIF REMAJA - Puspitawati, Herien; Defina, Defina; Musthofa, Musthofa; Naina, Sheila; Cahayani, Octaria Intan; Rahmah, Yazidah Nur; Maulina, Trisna; Habsari, Atika Windi (Jurnal Ilmu Keluarga dan Konsumen, 2021)
Fulfillment of the eight family functions through parent’s gender roles optimalization helps improve adolescents’ subjective well-being. The main objective of the study was to analyze the factors that influence adolescent’s subjective well-being using Structural Equation Modelling (SEM). The design of this study was a cross sectional study with data collection method was a voluntary non-probability sampling. The sample in this study were 277 adolescents from public middle school in Bogor City who live with their parents, consisting of 94 boys and 183 girls. The result showed that there was significantly difference in parent’s gender roles of the eight family functions between boys and girls. However, there was no significantly difference in subjective well-being between boys and girls. SEM Model showed that children’s characteristics latent variables influence adolescent’s subjective well-being directly and indirectly through parent’s gender roles. The latent variables of family characteristics also influence adolescent’s subjective well-being indirectly through parent’s gender roles. Finally, the latent variable of parent’s gender roles had a direct effect on adolescent’s subjective well-being. Therefore, parents are expectedly capable to formulate strategies to fulfill the intensity of activities and maximizing equal distribution of roles in the eight family functions for boys and girls without gender bias.